“Characteristics of Upper Gastrointestinal Tract Patients Undergoing Endoscopic Examination at Ibnu Sina Hospital, Makassar.” - AB, Tarisya Febriyanti Baso; Kanang, Indah Lestari Daeng; Sodiqah, Yani; Hidayati, Prema Hapsari; Iskandar, Darariani (Syifa'Medika, 2026)
Disorders of the upper gastrointestinal tract, such as heartburn, bleeding, and difficulty swallowing, are often experienced by many patients. Endoscopy is an important procedure in diagnosing disorders of the upper gastrointestinal tract. Ibnu Sina Hospital in Makassar routinely performs endoscopy on patients with these complaints, but data on the characteristics of patients undergoing this procedure in 2023 is not widely available. This study used a descriptive design with a cross-sectional approach. The sample consisted of 260 patients who underwent endoscopy for upper gastrointestinal complaints at Ibnu Sina Hospital in Makassar in 2023. Data were collected through patient medical records, which included demographic information, main complaints, and diagnoses found after endoscopy. The results showed that heartburn was the most common complaint (61.2%), followed by upper gastrointestinal bleeding (28.5%) and difficulty swallowing (5%). Gastritis was found to be the most common diagnosis (30.4%), followed by esophagitis and GERD (21.2%). Demographic factors such as age, gender, education, and occupation influenced the distribution of the disease. This study emphasizes the importance of a holistic approach in treating patients with upper gastrointestinal disorders, taking into account social, economic, and lifestyle factors. In addition, early detection through endoscopy needs to be improved to identify gastrointestinal problems more effectively.